PERLINDUNGAN SAKSI DAN KORBAN DALAM PROSES PENEGAKAN HUKUM PIDANA - Yudi Krismen (SISI LAIN REALITA, 2016)
Speaking about victims and witnesses, we can not be separated rather than criminal proceedings. In the provision of Article 184 paragraph (1) letter a witnesses KUHAP positioned as "evidence" that major in criminal matters. So consequently, in every process of law enforcement if the witness does not meet the legitimate calls from investigators, prosecutors until trial, the investigator, the prosecutor can conduct a forced effort to pick up the forced witnesses. Because, criminal proceedings are still bound by doctrine in introdusir Criminal Procedure Code, Criminal Procedure Code where the witness in the formulation of concentrating on "no probative value". However, with the enactment of Law No. 13 of 2006 on Protection of Witnesses and Victims, is expected to address issues of law against prolonged witnesses and victims in criminal proceedings.